TRADITIONAL GAMES AS A TOOL TO FULFILL THE RIGHT TO PLAY AND GOOD CHARACTER IN EARLY CHILDHOOD - Masganti Sitorus (Universitas Panca Sakti Bekasi, 2024)
Playing is a child's need equivalent to the need for work in adults. Therefore learning in early childhood should be done through play. However, to meet the demands of parents and the curriculum, sometimes learning in young children loses the feel of playing. This research was conducted at 10 schools that used traditional games to fulfill children's right to play while increasing children's good character. The research method uses a qualitative approach with observation and interview data collection methods. the results of the study show that children like games and develop good character after playing. The use of traditional games in meeting children's play needs needs to be discussed further. Besides that, traditional game design using digital game models also needs to be studied in the future.